Acupressure Points LI4 And SP6 For The Duration Of First Active Phase Of Labor Process - Dewi Kartika Sari Sari; Halimatus Saidah; Sri Lestari; Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Childbirth is a fisological thing that occurs in pregnant women, but some physiological conditions can change into pathological conditions if not appropriate handling. According to the East Java Health Profile in 2020 in 2019, the Maternal Mortality Rate of East Java Province reached 89.81 per 100,000 live births. This figure is up compared to 2020 which reached 98.39 per 100,000 live births (East Java Health Profile in 2020). The purpose of this study is to analyze the influence of Acupressure at LI4 and SP6 points on the length of first Active phase of labor process in Kediri City in 2021. The study used Pre-Experiments with posttest with control design. The population that will be used in this study is all maternity mothers in PMB Ny K Kediri City. Sampling techniques use sampling quotas. The sample count was 32 consisting of 16 for the control group and 16 for the treatment group. The results showed that the average length of labor in the control group was 259.94 minutes during first Active phase of labor process and the average length of labor in the treatment group was 212 minutes during first Active phase of labor process. From the different tests using the independent T test also obtained a p value of 0.000 which states that there is a difference between the control group and the treatment group with a time difference of 47.94 minutes faster in the treatment group. With the influence of acupressure at the point of LI4 and SP6 can be used as an alternative to accelerate the length of labor.